Exploration of Curriculum Management in Improving the Quality of Education at Integrated Islamic Junior High School Lukmanul Hakim - Nasruji (Yayasan Pendidikan Belajar Berdikari, 2025)
This study aims to explore the curriculum management at SMP Islam Terpadu Lukmanul Hakim and analyze how the curriculum management can improve the quality of education at the school. Using a qualitative approach, this study involved 50 respondents consisting of the principal, vice principal, teachers, students, and parents of students. Data were collected through in-depth interviews, field observations, and surveys. The results of the study indicate that the curriculum management at SMP Islam Terpadu Lukmanul Hakim has succeeded in integrating Islamic values ​​into every subject taught. The principal plays an important role in designing and supervising the character-based curriculum, as well as conducting regular training for teachers. However, the main challenge faced by teachers is the limited time and resources available to implement the curriculum effectively. The majority of students feel that the curriculum has a positive impact on their development, especially in strengthening character. This study concludes that although the curriculum management at SMP Islam Terpadu Lukmanul Hakim is quite good, several improvements need to be made, such as increasing teacher training, adjusting student workloads, and utilizing technology in learning. Thus, better curriculum management can contribute to improving the quality of education that is more optimal for students.